Effects of arginine and ornithine supplementation to a high‐protein diet on selected cellular immune variables in adult cats. (21st February 2020) - Paßlack, Nadine; Kohn, Barbara; Zentek, Jürgen
Abstract: Background: Dietary protein and amino acid intake and composition can modulate immune function. Objectives: To evaluate the effects of high‐protein intake and arginine and ornithine supplementation on feline immune cells. Animals: Ten healthy cats. Methods: Experimental study. Cats received a high‐protein basal diet as a single daily meal. A crossover design was applied with treatments being basal diet (w/o); basal diet with arginine supplementation (+50, 75, 100% compared to the arginine provision by the basal diet; Arg 1‐3); and basal diet with ornithine supplementation (+100, 150, 200% compared to the arginine provision by the basal diet; Orn 1‐3). Blood samples were collected at the end of each 11‐day treatment period. Results: Mitogen‐stimulated proliferative activity of blood leukocytes revealed a quadratic effect for the dietary supplementation of arginine ( P = .02) and ornithine ( P = .03) (means for ConA‐stimulation: w/o = 6.96; Arg 1 = 9.31; Arg 2 = 11.4; Arg 3 = 8.04; Orn 1 = 15.4; Orn 2 = 9.43; Orn 3 = 9.28; pooled SEM: 0.96). The number (% gated) of phagocytic granulocytes linearly decreased with increasing dietary concentrations of arginine ( P = .05) and ornithine ( P = .03) (means: w/o = 95.5; Arg 1 = 93.0; Arg 2 = 92.5; Arg 3 = 92.6; Orn 1 = 92.6; Orn 2 = 92.6; Orn 3 = 91.5; pooled SEM = 0.44). Conclusions and Clinical Importance: This study could demonstrate immunomodulating properties of dietary arginine and ornithine in cats.